(untitled) (Research, Society and Development, 2020)
Objective: To reveal the phenomenon of perception about the experience of people undergoing an amputation. Methods: Qualitative study, with a phenomenological approach. Data collection took place from April to December 2018, seven people were interviewed who were in the immediate postoperative period, admitted to a public hospital. Results: With the knowledge of the experience of the experience of the Being-amputee, he revealed that after the amputation the subject continues to perceive himself whole. Conclusion: With the loss of part of his body, the individual has his body image altered and for the acceptance of amputation and rehabilitation to occur satisfactorily, it is necessary that the multidisciplinary health team dedicates itself to qualified listening in addition to the aspects biophysiological aspects of the subject and make use of the trajectory experienced throughout the health-disease process.